STING in tumors: a focus on non-innate immune pathways - Yang, Jiaying; Yang, Mei; Wang, Yingtong; Sun, Jicheng; Liu, Yiran; Zhang, Ling; Guo, Baofeng (Frontiers in Cell and Developmental Biology, 2023)
Cyclic GMP-AMP synthase (cGAS) and downstream stimulator of interferon genes (STING) are involved in mediating innate immunity by promoting the release of interferon and other inflammatory factors. Mitochondrial DNA (mtDNA) with a double-stranded structure has greater efficiency and sensitivity in being detected by DNA sensors and thus has an important role in the activation of the cGAS-STING pathway. Many previous findings suggest that the cGAS-STING pathway-mediated innate immune regulation is the most important aspect affecting tumor survival, not only in its anti-tumor role but also in shaping the immunosuppressive tumor microenvironment (TME) through a variety of pathways. However, recent studies have shown that STING regulation of non-immune pathways is equally profound and also involved in tumor cell progression. In this paper, we will focus on the non-innate immune system pathways, in which the cGAS-STING pathway also plays